ANALISIS HUKUM ATAS WEWENANG PEMBERIAN IZIN PERTAMBANGAN EMAS OLEH PEMERINTAH PUSAT KE DAERAH DALAM PRESPEKTIF DAERAH OTONOM (Mimbar Keadilan, 2022)
The country of Indonesia is a country that has wealth derived from nature which is very abundant. This is evidenced by various types of commodities that can be exploited from mining to plantations. However, the wealth must be properly managed by the State and is intended entirely for the prosperity and welfare of the people. This management authority by the State must certainly be interpreted as fairly as possible. Considering that we are a country of laws, of course, in any case, it is mandatory to implement it in accordance with the basis of the existing guidelines of the rules. The concept of constitutional law, of course, we know the principle of regional autonomy. The division of authority between local government and central government has been formulated in detail in Law 23 of 2014 concerning Regional Government, LN.2014/No. 244, TLN No. 5587. These rules are the basis for granting authority, there are several things that need to be regulated by the Central Government and Regional Governments. This is done of course to create justice based on the laws that apply in Indonesia for all Indonesian people concretely. In this case, the author wants to elaborate on the granting of gold mining permits from the Central Government to local governments. The Autonomous Region, which used to have a role in the authority of gold mining permits, today the authority returns to the Central Government. The author wants to analyze whether the withdrawal of authority is not contrary to the spirit of the implementation of Regional Autonomy.